Brazil : 2017 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Brazil. (IMF Staff Country Reports; Country Report, 2017)
This 2017 Article IV Consultation highlights that Brazil's deep recession appears close to an end. The recession, triggered by large macroeconomic imbalances and a loss of confidence, was exacerbated by declining terms of trade, tight financing conditions, and a political crisis. Growth is projected to be 0.3 percent in 2017 and 1.3 percent in 2018, moving toward 2 percent in the medium term. Inflation is projected to undershoot its central target of 4.5 percent in 2017 and 2018. The forecast assumes that a sufficiently strong set of measures are put in place to ensure fiscal sustainability. Political instability and spillovers from the corruption investigation are major sources of risk that could threaten the reform agenda and the recovery.